2010
DOI: 10.1603/ec09202
|View full text |Cite
|
Sign up to set email alerts
|

Mortality of Four Stored Product Pests in Stored Wheat When Exposed to Doses of Three Entomopathogenic Nematodes

Abstract: The insecticidal effect of Heterorhabditis bacteriophora Poinar (Nematoda: Heterorhabditidae), Steinernema carpocapsae (Weiser) (Nematoda: Steinernematidae), and Steinernema feltiae (Filipjev) (Nematoda: Steinernematidae) against Mediterranean flour moth, Ephestia kuehniella (Zeller) (Lepidoptera: Pyralidae) (larvae), lesser grain borer, Rhyzopertha dominica (F.) (Coleoptera: Bostrychidae) (adults), rice weevil, Sitophilus oryzae (L.) (Coleoptera: Curculionidae) (adults), and confused flour beetle, Tribolium c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…We expect that satisfactory mortality rates of insects are the result of applying EPNs several times in a row. When applying EPNs several times in a row, one should of course take into account the economic aspect of food production (Athanassiou et al, 2010;Laznik et al, 2010c). The results of our study have shown that feeding of adult specimens of the greenhouse whitefly influences also the average mass of cucumbers (table 2) (Laznik et al, 2011).…”
Section: Greenhouse Whitefly (Trialeurodes Vaporariorum [Westwood])mentioning
confidence: 75%
“…We expect that satisfactory mortality rates of insects are the result of applying EPNs several times in a row. When applying EPNs several times in a row, one should of course take into account the economic aspect of food production (Athanassiou et al, 2010;Laznik et al, 2010c). The results of our study have shown that feeding of adult specimens of the greenhouse whitefly influences also the average mass of cucumbers (table 2) (Laznik et al, 2011).…”
Section: Greenhouse Whitefly (Trialeurodes Vaporariorum [Westwood])mentioning
confidence: 75%
“…Early studies evaluated the virulence of Steinernema feltiae Filipjev (formerly Neoplectana carpocapsae) (Alikhan et al 1985) and S. carpocapsae Weiser (Wójcik 1986) against adults of S. granaries. Various studies have also been conducted for the evaluation of the virulence of EPNs against the stored grain pest T. castaneum (Ramos-Rodríguez et al 2006) and the confused flour beetle, Tribolium confusum (Alikhan et al 1985;Athanassiou and Kavallieratos 2010;Rumbos and Athanassiou 2012). Larvae of T. castaneum were highly susceptible to three steinernematid species, i.e., S. feltiae, S. carpocapsae, and S. riobrave, whereas for pupae and adults, susceptibility was speciesdependent (Ramos-Rodríguez et al 2006).…”
Section: Resultsmentioning
confidence: 99%
“…However, most studies agree on the poor infectivity of EPNs against T. confusum adults (Athanassiou et al 2008;Rumbos and Athanassiou 2012). R. dominica larvae develop inside the kernel; hence, studies with EPNs have focused on the susceptibility of the freeliving adult stage, which exhibited low to moderate susceptibility (Ramos-Rodríguez et al 2006;Athanassiou and Kavallieratos 2010). Trdan et al (2006) also studied the effect of two heterorhabditid species, Heterorhabditis bacteriophora Poinar and H. megidis Poinar, Jackson and Klein, with H. megidis being the least efficient.…”
Section: Resultsmentioning
confidence: 99%
“…7,8 Entomopathogenic nematodes have been successfully applied as effective biological control agents against some significant lepidopteran, dipteran and coleopteran insects of commercial crops. 9 The effectiveness of entomopathogenic nematodes depends on both the nematodes' capability to locate, recognise and invade a host, and the virulence of the bacteria to susceptible hosts. 9 Entomopathogenic nematodes infect vulnerable insect hosts while in the free-living, non-feeding infective juvenile arrested developmental stage.…”
Section: Introductionmentioning
confidence: 99%
“…9 The effectiveness of entomopathogenic nematodes depends on both the nematodes' capability to locate, recognise and invade a host, and the virulence of the bacteria to susceptible hosts. 9 Entomopathogenic nematodes infect vulnerable insect hosts while in the free-living, non-feeding infective juvenile arrested developmental stage. Once in the gut of the host, they regurgitate or release their associated pathogenic bacteria into the haemocoel, resulting in septicaemia or toxaemia in the host within 24-48 h. 4 Upon infection, Steinernema infective juveniles develop into either feeding males or amphimictic females.…”
Section: Introductionmentioning
confidence: 99%